Rules for the correct use of Aymara orthography - Huayhua Pari, Felipe (2012)
The Aymara language has already entered a coding stage, and it has a long orthographic tradition, and has an official alphabet. But Aymara needs norms for writing (orthography) that take into account morphonology and syntax. The norms of writing must be based upon of the typology of Aymara Language.